Sebuah TANTANGAN STUNTING DI WILAYAH PEDESAAN: UPAYA PERCEPATAN PENURUNAN ANGKA STUNTING DI DESA LANGKAP, KABUPATEN JEMBER: TANTANGAN STUNTING DI WILAYAH PEDESAAN: UPAYA PERCEPATAN PENURUNAN ANGKA STUNTING DI DESA LANGKAP, KABUPATEN JEMBER - Yuniawati, Rizqy Aiddha (Jurnal Abdi Masyarakat Nusantara, 2023)
Globally, stunting is one of the targets of the Sustainable Development Goals (SDGs) which is in the process of realizing the second sustainable development goal, namely ending hunger, achieving better food security and nutrition, and supporting sustainable agriculture. The target included in this is an effort to reduce the stunting rate by 2025. Stunting needs to receive more attention because it can affect children's lives until they reach adulthood, especially increasing the risk of disrupting their physical and cognitive development if it is not treated properly immediately. This research aims to determine the level of stunting in Langkap Village, Bangsalsari District, Jember Regency. This activity aims to provide education and provide examples of how to reduce stunting rates from an early age. The method used for this service activity is the socialization method. Meanwhile, to analyze the results of pre-test and post-test data using quantitative methods. The results obtained are that pregnant women, expectant mothers and Langkap Village cadres know what causes babies to experience malnutrition, and how to prevent it from an early age. This was proven by the enthusiasm of the participants who asked questions in the question and answer session and also increased the value of the post-test results.